Construction and implementation of children’s psychological assistance programmes in the context of evidence-based psychotherapy - Valitova, Irina E.; Dyakov, Dmitry G. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article presents the programmes of psychological assistance to primary school children with behavioural and communication problems, which are designed on the basis of methodological principles of concrete-scientific level. The structure of the programme includes request for the assistance, analysis of the child’s problem on the basis of biopsychosocial model, the process of building therapeutic relationship, block of goals and tasks, description of the processes supporting the problem, programme modules with characteristics of the used complex methods of work with the child.
Keywords: cognitive-behavioural therapy; concrete-scientific level of methodology; psychological assistance to children; psychological assistance programmes; evidence-based psychotherapy; elementary school children; externalising behavioural disorders; selective mutism